2016
DOI: 10.4103/0973-1482.180687
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of head and neck cancer patients in Western Uttar Pradesh and analysis of distributions of risk factors in relation to site of tumor

Abstract: HNC accounts for 21.2% of total body malignancy and 47% of all malignancies in males and 2.5% in females. Squamous cell carcinoma was the most common histological type (97%). Maximum incidence of HNC (>60%) was in 40-60 year of age. Male:female ratio was 16:1. Oral cancers were most common HNC in patients below 40 year age group, whereas carcinoma oropharynx and larynx were more common in patients above 40 year age group. Tobacco smoking was a most prevalent risk factor for carcinoma oropharynx, larynx, and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 0 publications
5
31
1
Order By: Relevance
“…Male to female ratio of the registered HNC cases was 3.24:1 in the study conducted by George S Stoyanov et al 3 However, the study conducted by Mohammad Shadab Alam et al found the male to female ratio to be 16:1. 8 Our study concluded that squamous cell carcinoma is the most common histological type of carcinoma (87.78%). This is followed by adenocarcinoma and lymphoma.…”
Section: Risk Factorsmentioning
confidence: 61%
See 3 more Smart Citations
“…Male to female ratio of the registered HNC cases was 3.24:1 in the study conducted by George S Stoyanov et al 3 However, the study conducted by Mohammad Shadab Alam et al found the male to female ratio to be 16:1. 8 Our study concluded that squamous cell carcinoma is the most common histological type of carcinoma (87.78%). This is followed by adenocarcinoma and lymphoma.…”
Section: Risk Factorsmentioning
confidence: 61%
“…The main histopathological groups include squamous cell carcinoma 76.74% and adenocarcinoma 6.14% in the study conducted by George S Stoyanov et al 3 Similarly, the study conducted by Mohammad Shadab Alam et al found squamous cell carcinoma to be the most common Head and Neck carcinoma (97% cases). 8 While analysing the risk factors associated with Head and Neck carcinoma, we found that smoking and chewing together was the most common behavioural risk factor.…”
Section: Risk Factorsmentioning
confidence: 89%
See 2 more Smart Citations
“…Head and neck cancers (HNCs) are ranked as the sixth most frequent type of cancer worldwide. It is well known that tobacco and alcohol represent major risk factors for the development of HNCs (1), especially due to their synergistic effect. The human papilloma virus (HPV) is another well-known aetiology factor of some HNCs types and is associated with sexual practices (such as oral/genital/anal sex) (2).…”
Section: Introductionmentioning
confidence: 99%